Medial preoptic area in mice is capable of mediating sexually dimorphic behaviors regardless of gender - Yi-Chao Wei (Nature Portfolio, 2018)
The medial preoptic area (mPOA) in a mammalian brain is sexually dimorphic, and yet its exact function in mediating gender-specific behavior remains unclear. Here, Xu and colleagues show that optogenetic manipulation of the mPOA in male mice induce female-stereotyped behaviors and vice versa.